Another mechanism for creating diversity in gamma-aminobutyrate type A receptors: RNA splicing directs expression of two forms of gamma 2 phosphorylation site. - Whiting, P (1990)
Diversity of gamma-aminobutyrate type A (GABAA) receptors has recently been proposed to be achieved by assembly of receptor subtypes from a multitude of subunits (alpha 1-6, beta 1-3, gamma 1-2, and delta) encoded by different genes. Here we report a further mechanism for creating GABAA receptor diversity: alternative RNA splicing. Two forms of bovine gamma 2 subunit cDNA were isolated (gamma 2S and gamma 2L) that differed by the presence or absence of a 24-base-pair (8-amino acid) insertion in the cytoplasmic domain between the third and fourth putative membrane-spanning regions. Polymerase chain reaction from RNA demonstrated that the two forms of gamma 2 subunit are expressed in bovine, human, and rat brain. Sequencing of genomic DNA clones encoding the gamma 2 subunit demonstrated that the 24-base-pair insert is organized as a separate exon. Analysis of the sequence of the 8-amino acid insert revealed that it contains a protein kinase C consensus phosphorylation site. Expression of the large cytoplasmic loop domains of gamma 2S and gamma 2L in Escherichia coli, followed by phosphorylation of the recombinant proteins by protein kinase C, demonstrated that gamma 2L, but not gamma 2S, could be phosphorylated. Thus the two forms of gamma 2 subunit differ by the presence or absence of a protein kinase C phosphorylation site. This mechanism for creating GABAA receptor diversity may allow differential regulation of the function of receptor subtypes.